2021
DOI: 10.1021/acs.est.1c00883
|View full text |Cite
|
Sign up to set email alerts
|

Extractable Organofluorine Analysis in Pooled Human Serum and Placental Tissue Samples from an Austrian Subpopulation—A Mass Balance Analysis Approach

Abstract: Embryos and fetuses are of major concern due to their high vulnerability. Previous studies demonstrated that human exposure to per- and polyfluoroalkyl substances (PFAS) may be underestimated because only a limited number of known PFAS can be measured. This investigation studied the total PFAS exposure by measuring the extractable organofluorine (EOF) in pooled maternal serum, placental tissue, and cord serum samples (total number of pooled samples: n = 45). The EOF was analyzed using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Details of the LC and MS conditions are provided elsewhere. 35 The EOF were analyzed by combustion ion chromatography (CIC) (Metrohm, Switzerland), consisting of a combustion module, a 920 absorbent module and a 930 compact IC ex. In brief, the sample was placed in a quartz boat, and all uorine was converted to hydrogen uoride and absorbed into the water aer combustion at 1000-1050 C. The dissolved uoride was then analyzed by using the ion chromatograph.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…Details of the LC and MS conditions are provided elsewhere. 35 The EOF were analyzed by combustion ion chromatography (CIC) (Metrohm, Switzerland), consisting of a combustion module, a 920 absorbent module and a 930 compact IC ex. In brief, the sample was placed in a quartz boat, and all uorine was converted to hydrogen uoride and absorbed into the water aer combustion at 1000-1050 C. The dissolved uoride was then analyzed by using the ion chromatograph.…”
Section: Instrumental Analysismentioning
confidence: 99%
“…Per- and polyfluoroalkyl substances (PFAS) are a large and diverse group of anthropogenic chemicals with unique properties, such as stain-, oil-, and water repellency, and very high stability against extreme temperature and pH conditions, resulting from their strong C–F bonds. , These characteristics result in countless applications for PFAS, ranging from consumer products such as textiles, aqueous film-forming foams for firefighting to surfactants, and additives in industrial manufacturing. , Their widespread use resulted in the global distribution of perfluoroalkyl acids (PFAAs) in all environmental compartments including air, water, , and soil, as well as exposure of wildlife and humans . While the well-known PFAAs perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) are nowadays largely regulated as persistent organic pollutants due to their PBT properties (other long chain PFAAs are already proposed for listing), there are still more than 600 individual PFAS estimated to be on the global market and in daily use .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, two extensive PFASs, namely fipronil sulfone and 2-chloro-6-(trifluoromethyl)­pyridine-3-ol, were identified, contributing a median of 8.1% to the total quantified PFASs concentrations. The results might partially explain the unknown EOF in human blood reported in a previous study, and thus those chemicals should be included in further EOF analysis.…”
Section: Environmental Implications and Limitationsmentioning
confidence: 71%
“…13−15 However, mass balance analysis results showed that an average of 9% of extractable organofluorine (EOF) was unidentified in cord serum, indicating the presence of unknown PFASs in exposed fetuses. 16 Consequently, the novel PFASs identification in cord blood and their relationship with birth outcomes are essential to evaluate prenatal exposure risk of PFASs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation